Keypoints in Wound Contractures - Sudjatmiko, Gentur; Tania, Vika (Jurnal Plastik Rekonstruksi, 2012)
Wound contracture is a challenging problem to deal with. By understanding the phases of wound healing, attempts can be performed to prevent abnormal wound healing that can lead to scar contracture. This article will attempt to provide a simple summary of wound contracture and how to prevent it.Although most wounds can be expected to heal uneventfully, infection, dehiscence, and delayed healing continue to be problems, associated with signi!cant morbidity, mortality, and economic cost. Wound contracture is one of morbidities that caused by delayed healing and incorrect management of wound.